Prostacyclin induction by high-density lipoprotein (HDL) in vascular smooth muscle cells depends on sphingosine 1-phosphate receptors: Effect of simvastatin - González-Díez, María; Rodríguez, Cristina; Badimon, Lina; Martínez-González, José (Thrombosis and Haemostasis, 2008)
Prostacyclin (PGI2) is an important regulator of vascular homeostasis. Our goal was to analyze the role of sphingosine 1-phosphate (S1P) and its receptors in the up-regulation of cyclooxygenase-2 (Cox-2) induced by HDL in human vascular smooth muscle cells (VSMC). S1P induces Cox-2 expression in a time-and dose-dependent manner at concentrations (0.02–1 µM) compatible with those present in physiological HDL levels. The effect was mimicked by dihydro-S1P (DhS1P), a S1P derivative that only acts through cell surface S1P receptors. Desensitiz-ation of S1P receptors with S1P (or DhS1P) abolished HDL-induced Cox-2 up-regulation and PGI2 release. Inhibition of S1P receptors by suramin (inhibitor of S1P3), JTE013 (inhibitor of S1P2) or VPC23019 (inhibitor of S1P1 and S1P3) reduced the up-regulation of Cox-2 induced by HDL and S1P. The combination of suramin and JTE013 increased the inhibitory effect compared to that observed in cells treated with each inhibitor alone. siRNA against S1P2 or S1P3 significantly reduced the ability of HDL and S1P to up-regulate Cox-2. Simvastatin induced over-expression of S1P3 and potentiated the induction of Cox-2 expression produced by HDL (or S1P). Finally, suramin, JTE013 and VPC23019 inhibited p38 MAPK and ERK1/2 signaling pathways activated by HDL (or S1P) and the downstream activation of CREB, a key transcription factor involved in Cox-2 transcriptional up-regulation. These results indicate that S1P receptors, in particular S1P2 and S1P3, are involved in the Cox-2-dependent effects of HDL on vascular cells. Strategies aimed to therapeutically modulate S1P or S1P receptors could be useful to improve cardiovascular protection.
Keywords: Atherothrombosis; smooth muscle cells; lipoproteins; gene expression; antiplatelet agents